2023
DOI: 10.3390/ijerph20021410
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Workers after Two Years of COVID-19: The Consequences of the Pandemic on Psychological Health and Sleep among Nurses and Physicians

Abstract: COVID-19 has challenged the health workforce worldwide. In this cross-sectional study with a retrospective assessment, we explored the impact of the pandemic on mental health and sleep among a sample of Italian nurses and medical doctors. A total of 287 healthcare workers (212 nurses and 75 physicians) completed a web survey on socio-demographic, psychological, and sleep-related aspects referring to the period before the pandemic and to the present period of February to June 2022. Comparisons between nurses an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 51 publications
(63 reference statements)
1
10
0
Order By: Relevance
“…The advent of the COVID-19 pandemic, a highly transmissible zoonotic infection caused by SARS-CoV2, has resulted in a global health crisis not witnessed since the 1918 Spanish Flu Influenza pandemic 1 and consequences for both patients and healthcare workers 2 . Since clinical manifestations include a wide spectrum of signs and symptoms 3 —ranging from asymptomatic infections to acute respiratory distress syndrome and death—considerable efforts have been devoted to identifying the subset of patients at highest risk of disease progression 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The advent of the COVID-19 pandemic, a highly transmissible zoonotic infection caused by SARS-CoV2, has resulted in a global health crisis not witnessed since the 1918 Spanish Flu Influenza pandemic 1 and consequences for both patients and healthcare workers 2 . Since clinical manifestations include a wide spectrum of signs and symptoms 3 —ranging from asymptomatic infections to acute respiratory distress syndrome and death—considerable efforts have been devoted to identifying the subset of patients at highest risk of disease progression 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the impact of the COVID-19 pandemic on the mental health and sleep habits of Italian HCW, especially nurses and medical doctors, were evaluated by Alfonsi V et al (2023). The findings revealed that both groups were negatively affected by the pandemic, though nurses experienced a greater distress, with a significant worsening of various psychological and sleep-related symptoms over time [64] .…”
Section: Discussion and Resultsmentioning
confidence: 93%
“…A study done in Italy among healthcare professionals attributed sleep disturbances to psychological stress and women were at more risk. The study also stressed that better coping strategies must be adopted by healthcare professionals and healthcare institutes must reinforce them so that there are no long time mental health consequences after COVID infection among HCWs [ 31 ]. The preliminary research shows the possible reasons why repeated infections can alter the sleep cycle.…”
Section: Discussionmentioning
confidence: 99%